2011
DOI: 10.1128/iai.00950-10
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Salmonella enterica Serovar Typhimurium-Derived Outer Membrane Vesicles Delivering the Pneumococcal Protein PspA Confers Protection against Challenge with Streptococcus pneumoniae

Abstract: Gram-negative bacteria produce outer membrane vesicles (OMVs) that serve a variety of functions related to survival and pathogenicity. Periplasmic and outer membrane proteins are naturally captured during vesicle formation. This property has been exploited as a method to derive immunogenic vesicle preparations for use as vaccines. In this work, we constructed a Salmonella enterica serovar Typhimurium strain that synthesized a derivative of the pneumococcal protein PspA engineered to be secreted into the peripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
118
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 42 publications
4
118
0
Order By: Relevance
“…In addition, the possibility of engineering ETEC OMV to deliver heterologous molecules (6,22) that may not normally be vesicle associated could be an attractive option in the development of a broadly protective vaccine that incorporates multiple target antigens. Such a strategy is currently being examined by combining recombinant MenB proteins with Neisseria OMV (10).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the possibility of engineering ETEC OMV to deliver heterologous molecules (6,22) that may not normally be vesicle associated could be an attractive option in the development of a broadly protective vaccine that incorporates multiple target antigens. Such a strategy is currently being examined by combining recombinant MenB proteins with Neisseria OMV (10).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived dendritic cells (BMDCs) from C57BL/6 mice, generated in the presence of 2 ng/ml granulocyte-macrophage colony-stimulating factor, were incubated for 4 h with OMVs displaying Hbp (derivatives), purified Hbp-Ag85B CϩN -ESAT6-Rv2660c (200 g/ml), or synthetic peptide consisting of residues 241 to 260 of Ag85A (Ag85A 241-260 ) or residues 1 to 20 of ESAT6 (ESAT6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Thereafter, the BMDCs were washed three times and cocultured overnight with C57BL/6-derived T cell hybridoma cells (DE10) (50) that recognize the 1-A b -restricted Ag85A 241-260 peptide and cross-react with an I-A b -restricted peptide in Ag85B (Ag85B 281-300 ).…”
Section: Methodsmentioning
confidence: 99%
“…An increasing body of evidence suggests that extracellular antigens evoke im-mune responses superior to those of intracellular antigens (23)(24)(25). Recently, antibody responses to a heterologous antigen packaged into the lumen of Salmonella OMVs were observed to be lower than those to endogenous vesicle OMPs and LPS (20), suggesting that surface-exposed antigens may elicit superior immune responses also in vesicles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be necessary to enrich the OMV cargo with virulence determinants specific to the intracellular stage of infection (44,45) or with antigens that induce strong T cell responses (46)(47)(48). A number of studies have shown that expression and delivery of homologous and heterologous antigens with OMVs are feasible (45,49,50). We previously showed that immunization with B. pseudomallei OMVs stimulates memory T cell responses and gamma interferon (IFN-␥) production (14).…”
Section: Figmentioning
confidence: 99%